2004
DOI: 10.1007/s10384-004-0108-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topically Instilled Bunazosin Hydrochloride and Other Ocular Hypotensive Drugs on Endothelin-1-induced Constriction in Rabbit Retinal Arteries

Abstract: Under our experimental conditions, bunazosin and unoprostone inhibited the ET-1-induced constriction. Hence, bunazosin and unoprostone may be clinically more effective against ET-1-related retinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Okada et al. reported that only a single instillation of unoprostone partly inhibited the intravitreally injected ET‐1‐induced constriction of retinal vessels in rabbit eyes 50 . We intravitreally injected 20 µL of 5 × 10 −8 M ET‐1 to pharmacologically reduce the diameter of retinal vessels to about 30% of the pre‐injection diameter.…”
Section: Discussionmentioning
confidence: 83%
“…Okada et al. reported that only a single instillation of unoprostone partly inhibited the intravitreally injected ET‐1‐induced constriction of retinal vessels in rabbit eyes 50 . We intravitreally injected 20 µL of 5 × 10 −8 M ET‐1 to pharmacologically reduce the diameter of retinal vessels to about 30% of the pre‐injection diameter.…”
Section: Discussionmentioning
confidence: 83%
“…Although it has been reported that nipradilol inhibits ET-1-induced constriction in retinal arteries in rabbits (22), and that betaxolol has the same effect in human and porcine retinal arteries in vitro (48). Under our experimental conditions bunazosin and unoprostone were the only drugs examined that significantly inhibited ET-1-induced vasoconstriction (24). Hence, bunazosin and unoprostone may be clinically more effective in ET-1-related retinal diseases than other drugs.…”
Section: Effects Of Topically Instilled Bunazosin and Other Ocular Hymentioning
confidence: 53%
“…However, the mechanism of this effect is still unclear (40). Neither nipradilol nor betaxolol inhibited ET-1-induced constriction in our recent study (24). Although it has been reported that nipradilol inhibits ET-1-induced constriction in retinal arteries in rabbits (22), and that betaxolol has the same effect in human and porcine retinal arteries in vitro (48).…”
Section: Effects Of Topically Instilled Bunazosin and Other Ocular Hymentioning
confidence: 87%
See 1 more Smart Citation
“…Outros estudos demonstram um provável benefício para a hemodinâmica ocular da aplicação tópica da unoprostona, com potencial efeito anti-endotelina-1 e conseqüente inibição da constricção arteriolar retiniana (107)(108) ; do betaxolol, com potencial ação bloqueadora de canais de cálcio; e da dorzolamida, com potencial efeito na aceleração da circulação retiniana (99,(109)(110) . Em estudo com as drogas beta-bloqueadoras comumente prescritas no Brasil, foi demonstrado aumento estatisticamente significante no fluxo sangüíneo ocular com o uso de betaxolol, timolol e levobunolol, tendo sido maior com as duas últimas substâncias (111) .…”
Section: Modulação Do Fluxo Sangüíneounclassified